(untitled) (Bangladesh Journal of Bioethics, 2015)
Recently, Chinese researchers published the results of their research using a gene-editing technology on abnormal human zygotes. The research team believes this research has prospective clinical application, viz., for gene therapy for ?-thalassemia, a white blood cell disorder, and plan to persist with further studies, despite technical problems in this experiment. The research has elicited international criticism from both scientific and bioethics domains, because it innovates beyond the current global consensus against human germ line modification. This paper comments on some ethical issues presented by the research report and concludes that, under present circumstances, the Chinese research team did not meet a standard of scientific responsibility. Bangladesh Journal of Bioethics 2015 Vol.6 (1):22-26.